#BlackLivesMatter: A New Age of Student Activism - Downey, Dana (International Higher Education, 2020)
In the wake of the global outcry against police brutality and systemic injustice, university students globally are offering support and solidarity through activism. This builds on a history of students raising public consciousness about social issues and seeding policy change. These current events present an opportunity for global universities to catalyze public action by both addressing institutionalized racism themselves, and resourcing local efforts.